(3eNJUQ CHj eUYH CMeO Hf CHj HcQ GdRgQis - (3CMeO Hf CHj HcQ GdRgQj, CHh eUYHs ((3MSjf Hf jhSa YHO GdEeGe GdMce GdeSJfUQ s)
(3ChdgG (B:s
(3MOKfG EHh ESMGb GHQGgje GdeOjfi UGMH CHj gQjQI , bGd (B: (3MOKfG CHh eUYH CMeO Hf CHj HcQ GdRgQi bGd (B: (3GdMeO ddg GdPi HgOGg fgJOi s
(3BNQgG (B:s
(3hEPG YQHJ GdeQCI ai YOJgG ef WdGb ZjQ HGFf CdRe GdRhL cShJgG eGOGeJ ai YOJgG Ke eNJUQ CHj eUYH GdRgQi hGdMeO ddg cKjQkG s
(3QhGjI CHj GSMGb EHQGgje Hf SYjO Hf YKeGf GdeOfis
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(874 / 40) s
Keywords: (3Gdabg GdeGdcjs